2019
DOI: 10.1111/pce.13529
|View full text |Cite
|
Sign up to set email alerts
|

The role of plant species and soil condition in the structural development of the rhizosphere

Abstract: Roots naturally exert axial and radial pressures during growth, which alter the structural arrangement of soil at the root–soil interface. However, empirical models suggest soil densification, which can have negative impacts on water and nutrient uptake, occurs at the immediate root surface with decreasing distance from the root. Here, we spatially map structural gradients in the soil surrounding roots using non‐invasive imaging, to ascertain the role of root growth in early stage formation of soil structure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 53 publications
5
55
0
2
Order By: Relevance
“…1). This observation corroborates with a recent study that showed cracks associated with root formation (Helliwell et al 2019). However, soil texture profoundly influenced the soil structural development of planted soil: in sandy loam soil, porosity decreased constantly over the 6 weeks (from 15.4 to 7%) whereas, in clay soil, the porosity stayed constant over the 6 weeks (approximately 7.8%).…”
Section: Discussionsupporting
confidence: 92%
“…1). This observation corroborates with a recent study that showed cracks associated with root formation (Helliwell et al 2019). However, soil texture profoundly influenced the soil structural development of planted soil: in sandy loam soil, porosity decreased constantly over the 6 weeks (from 15.4 to 7%) whereas, in clay soil, the porosity stayed constant over the 6 weeks (approximately 7.8%).…”
Section: Discussionsupporting
confidence: 92%
“…All soil columns were scanned using a v|tome|x M 240 kV X-ray μCT scanner (GE Sensing & Inspection Technologies GmbH, Wunstorf, Image visualisation, soil pore, and root segmentation was conducted using VG Studio MAX (Volume Graphics GmbH, Heidelberg, Germany). The "Region Growing" tool in VG Studio MAX was used to interactively extract roots and artificial pores from the slices as has been described in Helliwell, Sturrock, Miller, Whalley, and Mooney (2019). As we only required segmentation of the artificial pore network and the unconnected roots, no further pre-or post-image processing steps were required.…”
Section: Ct Scanning Image Analysis and Data Collectionmentioning
confidence: 99%
“…The secretion of mucilage facilitates lubrication and reduces friction at the root-particle interface (Iijima et al 2004). Components of the mucilage can lower the surface tension of water and mucilage preserves liquid bridges in the rhizosphere that maintain root-soil contact and a zone of high water content around roots (Ahmed et al 2014;Burr-Hersey et al 2020;Carminati et al 2017Carminati et al , 2010Helliwell et al 2019;Kroener et al 2018;Moradi et al 2011;Read et al 2003). Root-induced particle movement and exudation act jointly to aggregate soil particles within the root-influenced zone.…”
Section: Introductionmentioning
confidence: 99%